Moderate Levels of Pretreatment HIV Drug Resistance — Zimbabwe, April–July 2015. (4th October 2017) - Da Silva, Juliana; Dzangare, Janet; Gonese, Elizabeth; Mhangara, Mutsa; Mugurungi, Owen; Barr, Beth; Lloyd, Spencer; Raizes, Elliot
Abstract: Background: The World Health Organization ( WHO) HIV Drug Resistance (HIVDR) report 2012 demonstrated that the levels of HIVDR to first-line antiretroviral therapy (ART) are increasing. This finding threatens to reverse a decade of gains in HIV/AIDS epidemic control. The WHO Global Action Plan for HIVDR emphasizes strengthening surveillance of drug resistance through the implementation of national cross-sectional surveys. We conducted such survey to determine the prevalence of HIVDR among ART-naive patients in Zimbabwe and to describe the profile of the surveillance drug resistance mutations (SDRM) encountered in the country. Methods: A prospective, nationally representative, cross-sectional survey was conducted in 35 clinical sites selected using two stage probability proportional to size sampling. Patients were enrolled during April–July 2015. Specimens were sent for genotyping to CDC Atlanta. SDRM were interpreted using Stanford HIV Drug Resistance Database classification. Results: A total of 361 subjects were surveyed. Most participants were female (60.3%) and the median age was 35.8 years. Thirty-four out of 361subjects presented with ≥1 SDRM (9.4%, 95% confidence interval: 6.8–12.8%) prior to initiation antiretroviral therapy (ART). Non-nucleoside reverse transcriptase inhibitor (NNRTI) mutations were the most commonly detected mutation ( n = 30). Only two patients presented with a nucleoside reverse transcriptase inhibitor mutation and one patient presented with a protease inhibitor mutation. In two patients, ≥3 SDRMs were detected, which may suggest they were not truly ART-naïve. Conclusion: This study provides national estimates of HIVDR in a high burden country with broad access to ART and provides valuable inisight on the state of HIVDR in such setting. Zimbabwe has reached moderate levels of HIVDR in ART-naive patients, as specified by the WHO classification. These levels may impact the ability to achieve viral suppression in a significant number of patients initiating standard ART regimens in Zimbabwe, where NNRTI-based regimens are used as the first line. The use of drugs with high resistance barrier, such as dolutegravir, may improve the care of patients in the developing world, where individualized pretreatment genotype is not feasible. Disclosures: All authors: No reported disclosures.